PERFORMANCE OF SPECIES Mabea fistulifera AND Eucalyptus urograndis WITH USE OF CELLULOSE RESIDUE IN DEGRADED AREAS - Giácomo, Romulo Guimarães; Alves, Marlene Cristina; Camara, Rodrigo; Pereira, Marcos Gervasio Gervasio; Souto Filho, Sebastião Nilce; Moraes, Mario Luiz Teixeira (Floresta, 2019)
The planting of forest species contributes to the recovery of degraded areas, and the use of industrial waste can favor this process. However, there is still little information on this aspect in Cerrado. The objective of this work was to evaluate the performance of seedlings of the native species Mabea fistulifera Mart. and of the exotic hybrid Eucalyptus urograndis, under fertilization with residue of the industrial production of cellulose, in monospecific plantations in degraded area. Fertilization treatments, applied in the planting line, were three doses of the residue (10, 15 and 20 Mg ha -1); conventional mineral fertilizer (NPK); absence of fertilization (control). The experimental design was a randomized block design, with a portion of subdivided parts: species in the portions (15 m x 60 m, n = 4 / species) and treatments in the subportions (15 m x 12 m, n = 1 / treatment / portion) total of 18 plants in each subplot. Survival rate and growth attributes (height, crown diameter, stem diameter at ground level) were evaluated for two consecutive years. The largest increases in seedling survival and growth of both species were provided by mineral fertilization, followed by the 10 Mg ha -1 dose of the residue, which should be the recommended.